Psychosocial interventions for treating depression and self-harm in adolescents: a systematic literature review - Nada Kusuma; Lutfiana Nur Azizah; Ghery Safitrah Fahrun; Dian Puspita Rizki (International Journal of Qualitative Research, 2026)
Depression and self-harm among adolescents are mental health issues that are on the rise globally and have a serious impact on adolescents’ social functioning, emotional development, and quality of life. Various risk factors such as adverse childhood experiences (ACEs), domestic violence, trauma, social isolation, attachment disorders, and psychosocial stress contribute to the onset of depression and self-harm among adolescents. This qualitative study aims to identify, analyze, and synthesize effective psychosocial interventions for addressing depression and self-harm in adolescents through a Systematic Literature Review (SLR) approach. The review followed the PRISMA guidelines, and relevant international journal articles published between 2023 and 2026 were searched through Scopus and Google Scholar. A total of 10 articles were selected based on inclusion criteria covering psychosocial interventions, adolescent mental health, childhood trauma, attachment, and psychosocial support from families and communities. The results indicate that psychosocial interventions based on attachment, trauma-informed care, cognitive behavioral therapy, family support, emotion regulation, community-based approaches, and multidisciplinary social support are effective in reducing depressive symptoms, enhancing resilience, improving emotion regulation, and reducing the risk of self-harm among adolescents. The involvement of families, schools, social workers, and the community environment is a critical factor in the success of these interventions. The findings emphasize that holistic, participatory, and trauma-informed psychosocial approaches are essential in social work practice with adolescents. This study recommends strengthening family-, school-, and community-based psychosocial intervention models as strategies for the prevention and management of depression and self-harm among adolescents.